Financial factors influencing growth of Horticultural sector in Nakuru County, Kenya - Kimani, Elijah M.; Tonui, J. K. (My University, 2016)
This study evaluated the financial factors influencing growth of horticultural sector in Nakuru County, Kenya. Of particular interest was the extent to which credit access and working capital affected the growth of horticultural firms. The study reviewed adverse selection theory and organizational theory of growth. A cross-sectional survey research design was adopted. The study targeted the 300 accounts, finance, and management staff working with the registered horticultural farms in Nakuru County. The sample size constituted 98 respondents. The study employed structured questionnaires. The research instrument was pilot tested. The data collected were subjected to relevant processing and analysis whereby the Statistical Package for Social Sciences software was used to aid in data analysis. Descriptive statistics tools were used. More so, inferential statistics were employed. The research hypotheses were tested at 0.05 level of significance. The findings of the study were presented in form of statistical tables. It was found that the influence of financial factors under study on growth of horticultural firms was significant. Working capital had the greatest influence on growth of firms. The study concluded that horticultural firms in Nakuru County highly invested in working capital and as such it influenced the firm’s liquidity. It was inferred that horticultural firms were able to access shortterm credit facilities. The study recommended that horticultural firms should source funds from various sources and negotiate for credit terms from such lenders as commercial banks. It is recommended that horticultural firms should effectively manage working capital.
Keywords: Access to credit; financial factors; firm growth; horticultural sector; working capital